Smart and Active Food Packaging: Insights in Novel Food Packaging - Ahari, Hamed; Soufiani, Solmaz P. (Frontiers in Microbiology, 2021)
The demand for more healthy foods with longer shelf life has been growing. Food packaging as one of the main aspects of food industries plays a vital role in meeting this demand. Integration of nanotechnology with food packaging systems (FPSs) revealed promising promotion in foods’ shelf life by introducing novel FPSs. In this paper, common classification, functionalities, employed nanotechnologies, and the used biomaterials are discussed. According to our survey, FPSs are classified as active food packaging (AFP) and smart food packaging (SFP) systems. The functionality of both systems was manipulated by employing nanotechnologies, such as metal nanoparticles and nanoemulsions, and appropriate biomaterials like synthetic polymers and biomass-derived biomaterials. “Degradability and antibacterial” and “Indicating and scavenging” are the well-known functions for AFP and SFP, respectively. The main purpose is to make a multifunctional FPS to increase foods’ shelf life and produce environmentally friendly and smart packaging without any hazard to human life.